Postpyloric decompression tube placement through a gastrostomy for malignant bowel obstruction - Kurita, Yusuke (BioMed Central, 2013)
BACKGROUND: Malignant bowel obstruction affect a patient’s quality of life, but, management of MBO is controversial. CASE PRESENTATION: A 51-year-old woman who had been diagnosed as uterine cervix cancer 2 years ago and had undergone surgery, chemotherapy and radiotherapy, was admitted to our hospital. She was diagnosed as having a recurrence of peritoneal metastasis and bowel obstruction. For her nasal pain, we considered insertion of a postpyloric decompression tube through the gastrostomy instead of via the nasal cavity. After insertion of a percutaneous gastrostomy tube was performed endoscopically, we introduced a postpyloric decompression tube through her gastrostomy. She could be discharged home, and 91 days later, she died in her home under hospice care, as she had wished. CONCLUSIONS: Insertion of a postpyloric decompression tube through a gastrostomy might be useful in the management of advanced cancer patients with bowel obstruction.